Human Resource Analytics And Strategic Decision-Making In Human Resource Management: A Systematic Literature Review - Drajat Sunaryadi (CV Pena Jaya Pers, 2025)
Purpose:This study aims to systematically review the role of Human Resource Analytics (HRA) in supporting strategic decision-making in Human Resource Management. Design/methodology/approach: A systematic literature review was conducted using peer-reviewed articles indexed in Scopus and SINTA, following PRISMA guidelines with defined inclusion and exclusion criteria. Findings:The results show that Human Resource Analytics enhances strategic HR decision-making in areas such as workforce planning, performance management, talent acquisition, and employee retention. Key dimensions frequently discussed include data quality, analytical capability, technological infrastructure, and managerial support. Research limitations/implications: This review is limited to selected databases and time periods. Future studies should apply longitudinal designs and examine mediating and moderating variables across different organizational contexts. Practical implications:Managers and HR practitioners can use Human Resource Analytics to improve evidence-based strategic HR decisions by strengthening analytical skills and data governance. Originality/value:This study provides an integrated overview of Human Resource Analytics and identifies key themes and directions for future research. Paper type:Literature review